Designing lesson plan of integer number operation based on fun and easy math (FEM) approach - Darin Fouryza; Siti Maghfirotun Amin; Rooselyna Ekawati (International Journal of Evaluation and Research in Education (IJERE), 2019)
This paper dealt with the design of learning tools, that was the development of learning implementation plan or Rencana Pelaksanaan Pembelajaran (RPP) based on Fun and Easy Math (FEM) approach in the form of a number line model. FEM was an approach in order to teach mathematics effectively to students in a fun and easy way according to the patterns and rules, making it easier for students to understand mathematical concepts and driving them to actively participate in learning activity. Furthermore, the number line model based on the rules aimed to provide the real idea of mathematical concept and avoid the mathematical manipulation. The design of RPP development was intended to create a new RPP which was divided into three activities, namely introduction, core, and closing. The method of lesson plan development used a Plomp’s development model which was consisted of three phases, namely preliminary research, prototype, and evaluation. The results of this development were expected to help students in understanding the mathematical concepts, namely integer calculation operations especially addition and subtraction, increasing student activeness in learning process, and avoiding the existence of mathematical manipulation.